"Goodness and Kindness": Long-Distance Caregiving Through Volunteers During the COVID-19 Lockdown in India. (28th October 2020) - Roy, Senjooti; Ayalon, Liat
Abstract: Objectives: The first Covid-19 lockdown in India was announced on March 24, 2020, with less than 4 hours' notice, leaving older adults without access to domestic help and paid caregivers. As traditional caregiving models ceased to function in the new setup, relatives of older adults turned to strangers and volunteers in an effort to provide urgent care to their older family members. This study explores the role of volunteers in meeting the immediate needs of older adults during the lockdown. Methods: A pan-India group of volunteers was formed during the lockdown on a popular social media website to connect people of all ages in need of help with those able to offer assistance. A sample of 242 messages pertaining to older adults was extracted for quantitative content analysis. Results: All but 2 requests were placed by adult relatives of older adults. Requests covered a number of needs, some of which were directly tied to the pandemic and lockdown, while others were general in nature but were greatly exacerbated by recent events. Discussion: The use of social media to encourage acts of kindness at a time of crisis was an innovative attempt to meet the immediate needs of older adults. The lockdown, however, exposed the lack of dedicated supports and services for older adults in India.